Echocardiographic Assessment of the Effect of Mitral Stenosis Severity on Left Ventricular Systolic Function Using Isololumic Myocardial Acceleration - Islam, Md Hasanul; Adhikary, Dipal Krishna; Parvin, Tanjima; Barman, Rabindra Nath; Rahman, Mahbubur; Sultan, Md Ashraf Uddin; Chowdhury, MSI Tipu; Hoque, Md Harisul (University Heart Journal, 2020)
Background: Isovolumic myocardial acceleration (IVA) is a new tissue Doppler parameter in the assessment of systolic function of both right and left ventricles. It remains unaffected with the changes in pre-and after load with in the physiological range. With the advent of newer parameter like IVA, better assessment are naturally expected. Thus it creates a fertile ground where upon many studies are being done as it chosen here. The aim of study was to assess the effect of MS severety on LV systolic function using IVA. Methods: In this cross sectional study, considering all ethical issues, data were collected from 96 patient (Isolated mitral stenosis and mitral valve area <2cm2) and 32 healthy control subjects. In addition to standard echocardiographic methods TDI (tissue Doppler imaging) were performed to assess LV function in all participants. Results: This study showed a clear female preponderence (76%) of mitral stenosis and most of them belonging to age group 21-39 years. All TDI derived LV systolic (IVV, Sm and IVA) velocities were significanty decreased in patients with mitral stenosis, compared to the healthy control (P<.001, for all). However IVA was not different when the degree of MS was evaluated (P=.056). In addition IVA was not correlated with MVA (r=+0.196. P= 0.056). Conclusions: Isovolumic myocardial acceleration was more accurate and consistent than conventional echocardiography in assessing subclinical left ventricular systolic dysfunction, IVA showed that left ventricular function is impaired with mitral stenosis regardless of severety of the disease. So this new echo parameter can be a good supplement to the existing 2D scoring system to detect systolic dysfunction in rheumatic mitral stenosis. University Heart Journal Vol. 17, No. 1, Jan 2021; 42-46